2014
DOI: 10.1007/s13311-014-0274-1
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation for Movement Disorders

Abstract: Deep brain stimulation (DBS) is an implanted electrical device that modulates specific targets in the brain resulting in symptomatic improvement in a particular neurologic disease, most commonly a movement disorder. It is preferred over previously used lesioning procedures due to its reversibility, adjustability, and ability to be used bilaterally with a good safety profile. Risks of DBS include intracranial bleeding, infection, malposition, and hardware issues, such migration, disconnection, or malfunction, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 124 publications
(121 reference statements)
0
77
0
2
Order By: Relevance
“…Our findings suggest that the STN LFP could provide a high-performance control signal for BMI driven neuroprosthetic grasping in paralysed patients, leveraging advances in surgery for deep brain stimulation which has now become a relatively safe procedure (Larson, 2014). Surgical subcortical targets, such as the STN and globus pallidus (GPi), are involved in motor planning and execution.…”
Section: Discussionmentioning
confidence: 92%
“…Our findings suggest that the STN LFP could provide a high-performance control signal for BMI driven neuroprosthetic grasping in paralysed patients, leveraging advances in surgery for deep brain stimulation which has now become a relatively safe procedure (Larson, 2014). Surgical subcortical targets, such as the STN and globus pallidus (GPi), are involved in motor planning and execution.…”
Section: Discussionmentioning
confidence: 92%
“…Deep brain stimulation (DBS) is a well-accepted procedure for the treatment of movement disorders such as Parkinson’s disease [156]. Recent groundbreaking studies have shown that DBS, which involves delivery of focal electrical current to specific neural structures within the brain, rapidly alleviates symptoms of depression [9, 10].…”
Section: Neural Circuitsmentioning
confidence: 99%
“…Patients with longstanding PD may have autonomic dysfunction, impaired respiratory reserve, sleep apnea, and increased risk for aspiration. 10 Autonomic dysfunction and levodopa therapy may lead to orthostatic hypotension.…”
Section: Preoperative Considerationsmentioning
confidence: 99%